Paramagnetic, near-infrared fluorescent Mn-doped PbS colloidal nanocrystals - Turyanska, Lyudmila; Moro, Fabrizio; Knott, Andrew N.; Fay, Michael W.; Bradshaw, Tracey D.; Patanè, Amalia (Wiley-VCH Verlag, 2013)
Mn-doped PbS colloidal nanocrystals in aqueous solution are paramagnetic and optically active in the technologically important biological window between 1.2 and 0.8 μm. Cytoxicity studies show that exposure of human cell lines to the nanoparticles at concentrations up to 0.2 mg mL−1 does not induce any adverse effect.